GENRE, ATTRIBUTION AND AUTHORSHIP IN THE THIRTEENTH CENTURY: ROBERT DE REIMS VS 'ROBERT DE RAINS'. (October 2019) - Saint-Cricq, Gaël
Abstract : This article presents a textbook case for the examination of generic interplay in the thirteenth century, investigating four works that offer transgeneric reworkings relating polyphony to trouvère song. These works are found as anonymous motets and clausulae in polyphonic gatherings, but their upper voices are also copied as multi-strophic songs in songbooks, where they are attributed to the trouvère Robert de Reims. This case therefore touches on the issues of generic borders and mixing, on trouvère involvement in this generic interplay, and on the relationships between attribution and authorship in the Middle Ages. The investigation has important outcomes for the reconstruction of the genetic map of the motet, revealing works playing havoc with the vectors of transmission customarily established in the interplay of motet, chanson and clausula, and revealing early trouvère involvement in the repertoire as an essential key to the comprehension of cross-over activity between song and polyphony.